2020
DOI: 10.3390/v12091045
|View full text |Cite
|
Sign up to set email alerts
|

RNAemia Corresponds to Disease Severity and Antibody Response in Hospitalized COVID-19 Patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a global health emergency. To improve the understanding of the systemic component of SARS-CoV-2, we investigated if viral load dynamics in plasma and respiratory samples are associated with antibody response and severity of coronavirus disease 2019 (COVID-19). SARS-CoV-2 RNA was found in plasma samples from 14 (44%) out of 32 patients. RNAemia was detected in 5 out of 6 fatal cases. Peak IgG values were significantly lower in mild/moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 36 publications
11
53
0
2
Order By: Relevance
“…In patients with fatal COVID-19 disease, approximately 60-70% have viremia, with detectable SARS-CoV-2 in the plasma by PCR [3,4], consistent with our observation that 73% of the patients had detectable SARS-CoV-2 in the myocardium at autopsy. In addition to the heart, previous studies utilizing RT-PCR on fresh tissue have shown similar levels of SARS-CoV-2 RNA in other organs throughout the Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In patients with fatal COVID-19 disease, approximately 60-70% have viremia, with detectable SARS-CoV-2 in the plasma by PCR [3,4], consistent with our observation that 73% of the patients had detectable SARS-CoV-2 in the myocardium at autopsy. In addition to the heart, previous studies utilizing RT-PCR on fresh tissue have shown similar levels of SARS-CoV-2 RNA in other organs throughout the Fig.…”
Section: Discussionsupporting
confidence: 90%
“…While coronavirus disease 2019 (COVID- 19), as caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), primarily affects the lungs [1,2], systemic viremia can occur in critically ill patients with COVID-19 [3,4]. Potential cardiac involvement by SARS-CoV-2 as indicated by dysrhythmias and acute heart failure with reduced ejection fraction has been reported [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV2 RNAemia has been associated with more severe COVID-19, including a higher probability of ICU admission and mechanical ventilation. However, in these studies disease severity was either heterogenous [ 27 ] and ARDS severity remained undefined, respectively [ 28 ]. Only a minority of patients enrolled in these studies actually required intensive care, whereas our study only included critically ill ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cycle thresholds of positive samples differed between survivors and non-survivors: Median cycles of oropharyngeal swabs were 35 (30)(31)(32)(33)(34)(35)(36)(37) in survivors and 30 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in non-survivors (p = 0.003). However, no significant difference was observed in tracheal swabs with 31 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) in survivors and 27 (24)(25)(26)(27)(28)(29)(30)(31)(32) in non-survivors (p = 0.11). Median cycles (IQR) in blood samples were equal in survivors and non-survivors (p = 0.613).…”
Section: Plos Onementioning
confidence: 99%
“…The correlation between the level of IgG titers and disease severity during the acute phase of COVID-19 is well described, as patients with a severe course of COVID-19 show higher levels of anti-spike 1 (S1) IgA and IgG than patients with mild course [36][37][38] is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%